Optimalisasi Perencanaan Pengelolaan Tempat Pengolahan Sampah Terpadu (TPST) di Desa Cangkringan Sukodono Sidoarjo - Sujatmiko, Dedi (Bisma : Bimbingan Swadaya Masyarakat, 2023)
The purpose of this community service is to assist the Village Government in planning the optimaslization of TPST Development. Through an action review approach, the result of this assistance is that the planning that has been formulated will help in facilitating the waste management of the Cangkringsari Sukodono Sidoarjo Village TPST. In this assistance, basic standards were also formulated in TPST operations, both planning related to the TPST business process and TPST drilling design to make it easier for stakholders to implement and realize environmentally friendly TPST in Cangkringsari Village, Sukodono District, Sidoarjo Regency.